An investigation into the classroom related schemata of trainee teachers educated at racially segregated schools. - Ralfe, Elizabeth Mary. (2011)
This thesis reports on an investigation of the schemata of trainee teachers from a range of different ethnic and language groups in KwaZulu-Natal who had been educated in racially segregated school systems. Informed by the insight that schemata are the products of life experience and that they constrain linguistic choices (see Tannen 1979), it was hypothesised at the outset that different ethnic groups have some different assumptions of what constitutes appropriate classroom behaviour and that this schematic knowledge is reflected in the surface linguistic forms used by teachers and pupils in classroom discourse. These differences in schemata could have unfortunate consequences for pupils of a different ethnic group from their teacher, and, in particular, those pupils from historically disempowered groups. Data was collected using an eclectic mix of quantitative and qualitative methods. Firstly, students responded to a questionnaire which elicited responses concerning pupil and teacher roles. This was followed by interviews with selected student teachers during which they were asked to comment on those statements in the questionnaire which exhibited the greatest differences between respondents who attended schools administered by racially different educational authorities. Finally, a story recall experiment was conducted. Respondents/subjects were all trainee teachers at a multi-racial college of education. The analyses of the findings of the quantitative questionnaire revealed significant differences between subjects from different education systems. The interview data, however, revealed that the differences were less marked than the findings of the questionnaire suggested. The analyses of the recall experiment suggested that while some differences between the subjects who had attended schools administered by racially segregated authorities do exist, these are not as great as initially hypothesised. Teachers need to be made aware of the problems inherent in cross-cultural encounters, and this awareness should be extended to pupils. This awareness, together with goodwill, should ensure that pupils having different schemata from their teacher and/or other pupils in the classroom will not be disadvantaged. === Thesis (M.A.)-University of Natal, 1997.